2018
DOI: 10.1021/acsomega.8b01277
|View full text |Cite
|
Sign up to set email alerts
|

Use of Protein Thin Film Organized by External Electric Field as a Template for Protein Crystallization

Abstract: The well-known difficulty to obtain high-quality protein crystals has motivated researchers to come up with new methods or modifications of established crystallization methods to stimulate the growth of good diffracting crystals. In the present work, a new approach, using a protein thin film organized by external electric field (EEF) as a template for protein crystal growth, is introduced. This method increased nucleation of hen egg white lysozyme (HEWL) in comparison with the classical vapor diffusion method,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…, and M jk (z) is defined as (11) Based on their estimators under the ergodicity with the large enough values of k and T, Equations (10) and (11) could be solved to obtain [49]:…”
Section: Finite-temperature Stringmentioning
confidence: 99%
See 1 more Smart Citation
“…, and M jk (z) is defined as (11) Based on their estimators under the ergodicity with the large enough values of k and T, Equations (10) and (11) could be solved to obtain [49]:…”
Section: Finite-temperature Stringmentioning
confidence: 99%
“…Recently, external electric fields have been an effective tool to induce variations in phase transformations [ 1 , 2 ], with the formation of a potential new crystal phase and morphology, so as to realize control of the production process and improvements in the structures and properties of materials [ 3 , 4 , 5 , 6 , 7 ]. As mentioned by Alexander et al [ 8 ], electric fields can reduce the nucleation time [ 9 , 10 , 11 ], increase the product yield [ 12 , 13 , 14 ], enhance overall crystal quality [ 10 , 13 , 15 , 16 ], and control the location of nucleation [ 16 ], the product crystal size [ 10 , 17 , 18 ], the crystal orientation [ 19 , 20 , 21 ] and polymorphism [ 22 , 23 , 24 , 25 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Effects resulting from the application of AC fields on crystallization have also been studied by Hou and Chang, 15 Li and Lakerveld, 53 and a series of publications by Koizumi et al 16,24,25,31,33,34,51 Each author contributed findings on an effect of the applied electric field on the crystallization process. It has been demonstrated that application of electric fields have the ability to control both an increase and a reduction in the rate of nucleation 19,24,29,30,36,37,43 and crystal size, 7,14,17,19,26,29,57 an increase in the final crystal quality was obtained, [14][15][16][17]19,25,50 improved X-ray diffraction signal-tonoise ratio was observed, 41,42 and control of crystal orientation 14,30,36,37,43,57 and polymorphic form. 2,11,12,59,60 The findings drawn from past studies show in general, positive effects on the behavior of crystal growth under application of an electric field.…”
Section: Discussionmentioning
confidence: 99%
“…48 External AC electric field There are many examples of research focusing on the use of DC external fields to control nucleation. 2,11,13,17,19,36,37,49,50 These articles have primarily demonstrated a reduction in the nucleation rate with an applied electric field. Nonetheless, making use of an external AC electric field with suitable frequency to successfully control an increase and a reduction in the rate of nucleation for crystallization processes had not been accomplished until the work of Koizumi et al 24 in 2009.…”
Section: Internal DC Electric Fieldmentioning
confidence: 99%
“…To reduce this effect, microgravity has been employed to create a diffusion-controlled crystallization environment; however, protein crystallization is challenging in microgravity-based conditions. Although protein crystals that are formed under a microgravity environment have shown improvements in resolution, mosaicity, and other crystallographic parameters, a true microgravity environment only exists on the International Space Station. Therefore, the development of imitated microgravity conditions on the ground including appropriate magnetic and electric fields has provided a more accessible approach to obtaining high-quality protein crystals for the collection of precise three-dimensional (3D) structural data. …”
Section: Introductionmentioning
confidence: 99%